The Role of Hypothyroidism in the Etiology and Progression of Dilated Cardiomyopathy in Doberman Pinschers. (10th October 2014) - Beier, P.; Reese, S.; Holler, P.J.; Simak, J.; Tater, G.; Wess, G.
<x xml:space="preserve">Abstract</x> Background Hypothyroidism and dilated cardiomyopathy (DCM) are both common diseases in Doberman Pinschers. A possible influence of hypothyroidism on the etiology and progression of DCM is controversial. Objectives Evaluation of the role of hypothyroidism in etiology and progression of DCM. Animals A total of 175 Doberman Pinschers. Methods In this longitudinal prospective study, echocardiography and 24‐hour ambulatory ECG recordings were performed in all dogs as screening tests for DCM. Total thyroxine (TT4) and thyroid ultrasonography served as initial screening tests for hypothyroidism and low TT4 values were followed up by a thyroid stimulating hormone (TSH) test or free total thyroxine (fT4)/cTSH measurements. Additionally, a follow‐up study of dogs affected by both DCM and hypothyroidism under optimal treatment for hypothyroidism was conducted. Results A total of 107 dogs were healthy, 45 dogs had DCM, 11 hypothyroidism, and 12 dogs had both DCM and hypothyroidism. TT4 values as well as the thyroid volumes were equivalent in the healthy dogs and in those with DCM. Neither ventricular premature complexes nor echocardiographic parameters differed between healthy and hypothyroid dogs. Dogs with DCM had a 2.26‐fold (CI0.95 = 1.1–4.8) higher risk of also being affected by hypothyroidism. Despite optimal thyroid treatment of dogs with hypothyroidism and DCM, there was a progression of the heart disease. Conclusions and Clinical Importance This study did not confirm a role of hypothyroidism in the etiology or progression of DCM. Treatment of hypothyroidism did not improve the clinical outcome.